2017
DOI: 10.18632/oncotarget.23722
|View full text |Cite
|
Sign up to set email alerts
|

C-Kit receptor and tryptase expressing mast cells correlate with angiogenesis in breast cancer patients

Abstract: C-Kit protein is a transmembrane tyrosine kinase (TK) receptor (c-KitR-TK), which is predominantly expressed on mast cells (MCs) playing a role in tumor angiogenesis. It could be also expressed on epithelial breast cancer cells (EBCCs), but no data have been published regarding the correlation between mast cells positive to c-KitR (MCs-c-KitR), EBCCs positive to c-KitR (EBCCs-c-KitR), BC angiogenesis in terms of microvessel density (MVD) and the main clinic-pathological features. This study aims to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…These immune structures represent an important immune barrier against many economically significant pathogens that replicate in the intestinal epithelium. Non-lymphoid components of the immune system include cells that provide a non-specific immune defense of the host (Qureshi et al 1998;Marech et al 2018). Klasing (1998) reports that factors related to bird genetics, frequency of their exposure to pathogens, and effectiveness of vaccination programs influence the incidence of infectious diseases in birds.…”
Section: Introductionmentioning
confidence: 99%
“…These immune structures represent an important immune barrier against many economically significant pathogens that replicate in the intestinal epithelium. Non-lymphoid components of the immune system include cells that provide a non-specific immune defense of the host (Qureshi et al 1998;Marech et al 2018). Klasing (1998) reports that factors related to bird genetics, frequency of their exposure to pathogens, and effectiveness of vaccination programs influence the incidence of infectious diseases in birds.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, tryptase was found to induce in vitro endothelial cell proliferation in matrigel assay. 12 This was supported by other studies in which it was observed that tryptase promoted endothelial progenitor cell (EPC) migration which was inhibited when tryptase inhibitors were used. Tryptase was found to promote endothelial tube formation and this significantly increased VEGFR-2 RNA levels in EPC which was reversed when treated with tryptase and PAR-2 inhibitors.…”
Section: Tryptase As a Marker Of Angiogenesis In Solid Tumorsmentioning
confidence: 55%
“…Generally speaking, c-kit expression is the most commonly used staining technique to study the role of mast cells in peripheral nerve sheath tumors, [34][35][36] certainly because c-kit driven mast cell activation promotes the release of tryptase, the most important pro-angiogenic factor. 42,43 Canine models confirmed such assumption by demonstrating the correlation of c-kit expression to the degranulated status on mast cells. 43 For breast cancer, mast cell staining for c-kit and tryptase are essentially the same due to an almost perfect correlation suggesting that c-kit expression represents tryptase activation.…”
Section: Discussionmentioning
confidence: 67%
“…Such observation has a potential therapeutic role in the way that it could characterize a novel anti-angiogenic target for either c-kit receptor or tryptase inhibitors in patients having elevated c-kit expression. 42 Similar to MCD, Ki-67 LI shows a relatively similar distribution in tumor core and periphery regardless of the NF1 status. In addition, it has no correlation with the outcome.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation